Persuasive Discourse: Metadiscourse Practices in Chinese Live Streaming - Chen, Qian; Li, Yaping (Vestnik NSU. Series: History and Philology, 2025)
In e-commerce live streaming, businesses are increasingly turning to “TikTok short video + live streaming”, which features as a key marketing method. This study attempts to investigate how persuasive discourse is constructed in this genre through metadiscourse practices. By drawing on Hyland’s (2005) interactional models of metadiscourse and Verschueren’s (1999) metapragmatic awareness theory, this study examines the pragmatic functions of persuasive discourse and the metapragmatic awareness of the streamers reflected on TikTok. This research provides streamers with insights on how to achieve their marketing goals more effectively by enhancing their own metapragmatic awareness and using appropriate practices of persuasive discourse.